Coriolis Vibratory Gyroscopes Theory and Design - Apostolyuk, Vladislav; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides the latest theoretical analysis and design methodologies of different types of Coriolis vibratory gyroscopes (CVG). Together, the chapters analyze different types of sensitive element designs and their kinematics, derivation of motion equations, analysis of sensitive elements dynamics in modulated and demodulated signals, calculation and optimization of main performance characteristics, and signal processing and control. Essential aspects of numerical simulation of CVG using Simulink® are also covered. This is an ideal book for graduate students, researchers, and engineers working in fields that require gyroscope application, including but not limited to: inertial sensors and systems, automotive and consumer electronics, small unmanned aircraft control systems, personal mobile navigation systems and related software development, and augmented and virtual reality systems.
Introduction -- Motion Equations of Coriolis Vibratory Gyroscopes -- Sensitive Element Dynamics -- CVG Dynamics in Demodulated Signals -- Sensitive Element Design Methodologies -- Signal Processing and Control.
Keywords: Engineering; Nanoscale science; Nanoscience; Nanostructures; Nanotechnology; Control engineering; Electronics; Microelectronics; Engineering; Electronics and Microelectronics, Instrumentation; Nanotechnology and Microengineering; Nanoscale Science and Technology; Control; Electronic books